European debt crisis: analysis and problems of the external debt of the EU countries - Shuba, Olena; Topal, T. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article examines the importance of studying the situation, which is the result of the EU debt crisis, considers the debt structure of the countries which faced the worst crisis consequences, determines certain causes of rapid deterioration of the debt obligations in the EU countries.